2019
DOI: 10.1093/jas/skz010
|View full text |Cite
|
Sign up to set email alerts
|

The quality of the algorithm for proven and young with various sets of core animals in a multibreed sheep population1

Abstract: The inverses of the pedigree and genomic relationship matrices (A, G) are required for single-step GBLUP (ssGBLUP). While, inverting A is possible for millions of animals at a linear cost, inverting G has a cubic cost and feasible for at most 150,000 animals, using the current conventional algorithms. The algorithm for proven and young (APY) provides approximations of the regular ssGBLUP by splitting genotyped animals into core and noncore groups, with computational costs being cubic for core and linear for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Their approach with the QR decomposition of SNP genotype matrix choose a core subset that improved convergence, but it did not improve accuracy. Nilforooshan and Lee [15] used the diagonal construction based on G as well as based on A . They found that the diagonal construction based on G gave similar correlation between GEBVs from the full inverse and APY inverse, when the core subset was large, but worse with smaller core subsets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their approach with the QR decomposition of SNP genotype matrix choose a core subset that improved convergence, but it did not improve accuracy. Nilforooshan and Lee [15] used the diagonal construction based on G as well as based on A . They found that the diagonal construction based on G gave similar correlation between GEBVs from the full inverse and APY inverse, when the core subset was large, but worse with smaller core subsets.…”
Section: Discussionmentioning
confidence: 99%
“…During model fitting, phenotype information “flows” between both subsets of animals, hence both subsets contribute to the estimation. While APY is an approximation, it has been shown to be accurate and scalable for various populations of dairy and beef cattle [11, 12], pigs [13, 14], and sheep [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Animals were sorted in genealogical order and then core animals were uniformly sampled across the pedigree. Since is a sparse representation of [ 14 , 16 , 17 ], sampling animals across generations has the potential to capture all (co)variation in .…”
Section: Methodsmentioning
confidence: 99%
“…In a seminal study, Misztal [ 11 ] hypothesized that the accuracy of APY depends on how well animals in the core group represent the independent chromosome segments (ICS) that are present in the population. Several studies have investigated the core definition in APY ssGBLUP [ 2 , 12 17 ]. Some have reported that, in cattle, using proven bulls as core led to nearly identical accuracy as using randomly selected core sets [ 2 , 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation